Identity between painting and sculpture in cylinder seals (Akkadian era) (Journal of the College of Basic Education, 2022)
The current research tagged (Identity between painting and sculpture in cylinder seals (Akkadian era) constitutes an objective study in cylinder seals and painting in the Akkadian era, investigating the basic styles, types and ideas inherent in the construction of these cylinder seals and their identification with the art of drawings, the research dealt with four chapters, related to The first of them is in the methodological framework, in which the problem, importance, objectives and limits of the research and definition of terms are defined, in order to clarify the concepts.The research problem posed by the researcher was represented by the following question:What is the similarity between painting and sculpture in cylinder seals? (Akkadian era)?In addition to that, the importance of the research and the need for it. The aim of the current research is to:- Identifying the identification between painting and sculpture in cylinder seals (Akkadian era).The second chapter included the theoretical framework in two sections, the first topic concerned: the concept of identification, while the second topic dealt with the mechanism of the work of the gender of art on cylinder seals, and the theoretical framework was sealed with a set of indicators. The third chapter was concerned with research procedures, and represented in: the research community: Where it was limited to a set of Akkadian cylinder seals, within the limits of the research, and (3) models and analysis of the current research sample models were selected according to the analytical descriptive approach. Among the results, the most important of them are: 1- The cylinder and flat seals constituted a milestone in the cultural and artistic production of the ancient Iraqi civilization, due to its design and aesthetic characteristics, and this is what was stated in the whole sample.2- The seals were characterized by several formal features based on anecdotal scenes from reality and imagination, affirmation of ideological action and daily life, and representing the gods. As in all sample models.